Impact Evaluation of the Use of Mercury (Hg) and Cyanide (Cn) in Gold Processing Activities on Lombok Island Based on Knowledge and Experience of Gold Miners and Processers on Lombok Island - Hilman Ahyadi; Suripto Suripto; Ahmad Jupri; Immy Suci Rohyani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
The high value and economic prospects of precious metals, have not been able to cover the environmental, health and social and economic impacts. The conversion of land functions and open pit mining activities as well as the amount of sediment waste causes very significant landscape and environmental changes. This study aims to evaluate the impact of using mercury and cyanide based on the knowledge and experience of actors (miners and gold processors) and the surrounding community on the island of Lombok. Field data collection was carried out by triangulation, namely in-depth interviews with actors and the community, and secondary/reference data from related agencies, especially the health center and several related research results. Gold extraction on the island of Lombok uses two methods which are carried out in stages, namely Amalgamation with mercury in the shelling process and Cyanidation with Potassium Cyanide in the bagging process. The results of the study show that the negative impacts of the mining process are more due to land clearing and miner safety. The impact of gold extraction using mercury is long-term, so it is difficult to identify the impact. Meanwhile, the impact of the use of cyanide is directly felt and seen by the public, especially in terms of decreasing the presence and yield of fish caught in rivers and coasts.